STATE GOVERNMENT RELATIONS LEGISLATIVE COUNSEL BRIEFING BOOK (Tufts Archival Research Center, 2007)
RJR State Government Relations Briefing book for Attorney Law firms. Describes the make-up of the Tobacco Institute and highlights the mission of the State Activities Division. Reports on State Legislative programs mentioning the Labor Management Committee (LMC), environmental tobacco smoke (ETS) and indoor air quality (IAQ) experts, fire service organization, workplace smoking, advertisement /sampling, and continued work on issues such as excise tax, marketing, and smoking restrictions.